2013
DOI: 10.1016/j.tsf.2012.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of Cu2ZnSnS4 thin film absorbers from ZnS and Cu3SnS4 nanoparticle precursors

Abstract: Cu2ZnSnS4 (CZTS) has been considered as an alternative absorber layer to Cu(In,Ga)Se2 due to its earth abundant and environmentally friendly constituents, optimal direct band gap of 1.4-1.6 eV and high absorption coefficient in the visible range. In this work, we propose a solution-based chemical route for preparation of CZTS thin film absorbers by spin coating of the precursor inks composed of Cu3SnS4 and ZnS NPs and annealing in Ar/H2S atmosphere. X-ray diffraction and Raman spectroscopy were used to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 25 publications
10
27
0
Order By: Relevance
“…The study also revealed that there is a decrease in optical band gap with increasing Cu/(Zn + Sn) ratio of the CZTS thin film. This is in accordance with previous reports [19,20]. …”
Section: Optical Propertiessupporting
confidence: 94%
“…The study also revealed that there is a decrease in optical band gap with increasing Cu/(Zn + Sn) ratio of the CZTS thin film. This is in accordance with previous reports [19,20]. …”
Section: Optical Propertiessupporting
confidence: 94%
“…After a correction for the instrumental broadening, an average value of the crystallites is found to be 11-14 nm. These results are in a good agreement with those obtained by Lin et al [19]. It The Fig.…”
Section: Structural Propertiessupporting
confidence: 92%
“…It is observed that the CTS film prepared using a concentration of Cu 2+ of 15 mM, exhibit Raman peaks at 289, 300, 335 and 353 cm -1 which have been assigned to the A' symmetry vibrational modes from the tetragonal Cu 2 SnS 3 phase. [20][21][22][23] In addition, this sample exhibits a peak at 315 cm -1 which also has been assigned to the monoclinic Cu 2 SnS 3 phase. However, other authors have observed peaks at 290, 314 and 352 cm -1 which were assigned to monoclinic Cu 2 SnS 3 .…”
Section: Resultsmentioning
confidence: 77%